(untitled) (Applied Biological Research, 2019)
Anthocyanins, the flavonoid group of polyphenols, is in great demand as an important food constituent, mainly due to its health promoting attributes. The present study was undertaken with 11 newly developed coloured grape hybrids at ICAR-IARI, New Delhi (India). Efforts were made to identify and quantify different anthocyanin fractions. HPLC chromatogram revealed ten different peaks belonging to anthocyanins, which varied significantly from 37.68 to 247.68 µg g-1in terms of C3G equivalent. The maximum peak height was at peak-5, which represents malvidin-3-glucoside. Maximum anthocyanin content was in grape hybrid ‘Hy.16/2A-R1 P18’. The anti oxidant activities of hybrids were measured by FRAP assay. The hybrid ‘Hy.16/2A-R1P19’ was found the most potent antioxidant rich genotype in terms of FRAP. The potential genotypes identified in terms of high bioactive contents can be helpful in protection against various chronic diseases.